2012
DOI: 10.1186/1471-2407-12-559
|View full text |Cite
|
Sign up to set email alerts
|

Physical and psychosocial benefits of yoga in cancer patients and survivors, a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundThis study aimed to systematically review the evidence from randomized controlled trials (RCTs) and to conduct a meta-analysis of the effects of yoga on physical and psychosocial outcomes in cancer patients and survivors.MethodsA systematic literature search in ten databases was conducted in November 2011. Studies were included if they had an RCT design, focused on cancer patients or survivors, included physical postures in the yoga program, compared yoga with a non-exercise or waitlist control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
283
2
20

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(315 citation statements)
references
References 64 publications
10
283
2
20
Order By: Relevance
“…29 It is also important to highlight that only 35.71% (n=5) of the studies reported the process of masking of subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 It is also important to highlight that only 35.71% (n=5) of the studies reported the process of masking of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…28 This could have influenced the results of those studies that did not show significant results in favor of yoga since, in general, they had a short duration. 29 Yoga is an ancient practice that has its origin in India. Its practice typically combines physical postures (asanas), breathing exercises (pranayama) and meditation techniques (dhyana).…”
Section: Discussionmentioning
confidence: 99%
“…Among these fifty seven were clinical trials; forty were randomized control trials, thirty eight systematic reviews and five Meta analyses. Evidence from these studies and metanalysis show benefit finding for the effect of yoga interventions in managing cancer treatment related distress, mood states, quality of life and symptoms [6,7].…”
mentioning
confidence: 94%
“…In addition, a meta analysis of breast cancer survivors from 16 studies found that those who got the recommended 150 minutes of exercise each week had an 11% reduction in breast cancer mortality, and a 24% lower risk of overall mortality [19]. In addition, remaining physically active during recovery from breast cancer can also help to improve quality of life, body image, mood, bone health, and physical condition, while at the same time reducing fatigue, stress, and anxiety [20][21][22][23][24][25][26]. In light of this and other findings, the American Cancer Society has made the following recommendations for breast cancer survivors to maintain their weight [27]:…”
Section: Physical Activity Recommendationsmentioning
confidence: 99%